Uso de probióticos em ração de rã-touro (Rana catesbeiana): Desempenho produtivo - Dias, D. C. [UNESP]; Stéfani, M. V. [UNESP]; Ferreira, C. M.; França, F. M. (My University, 2008)
This experiment had as objective to evaluate the effect of two probiotics, added in the commercial ration (40% PB) on the productive performance of bullfrog Rana catesbeiana. The test was lead with two dosages of each probiotic (5 g/kg of food and 10 g/kg of food), plus a control group, with three repetitions, totalizing five treatments. The weight gain, the feed conversion (CA) and the specific growth rate (TCE) have been analyzed. The results show that the probiotics affect the weight gain of Rana catesbeiana until reaching 200 g, thus decreasing the time of productivity in 28 days but not improving the CA and the TCE. With bases in these experimental conditions probiotic 1 (Lactobacillus acidofillus, Bifidobacterium bifidum and Enterococcus faecium -3×10 6 UFC/g) at lower dose (5 g/kg of ration) provided the best performance of the animals.
Use of probiotics in the ration of bullfrog (Rana catesbeiana): Productive performance
Keywords: Alimentary supplements; Feed conversion; Weight gain; Animalia; Anura; Bifidobacterium bifidum; Enterococcus faecium; Lactobacillus; Rana catesbeiana